Antibacterial activity of bioactive compounds extracted from red kidney bean (Phaseolus vulgaris L.) seeds against multidrug-resistant Enterobacterales - Ebrahim, Azhar E.; Abd El-Aziz, Norhan K.; Elariny, Eman Y. T.; Shindia, Ahmed; Osman, Ali; Hozzein, Wael N.; Alkhalifah, Dalal Hussien M.; El-Hossary, Dalia (Frontiers in Microbiology, 2022)
In the present study, biologically active compounds such as phenolic-rich extract (PRE), 7S globulin (vicilin), and 11S globulin (legumin) from red kidney bean (Phaseolus vulgaris L.) seeds were extracted and evaluated as antibacterial agents against multidrug-resistant (MDR) Enterobacterales isolated from both animal and human sources. The overall occurrence rate of Enterobacterales was 43.6%, which significantly differed between animal (38.75%) and human (56.67%) sources. Antimicrobial susceptibility testing revealed that Enterobacterales isolates exhibited full resistance (100%) to amoxicillin-clavulanic acid, followed by ampicillin (75.44%), erythromycin (71.93%), cefoxitin (70.18%), amoxicillin (66.66%), ceftriaxone (64.91%), and trimethoprim/sulfamethoxazole (56.14%). Worthy of note, 97.92% of Enterobacterales isolates were MDR. The total phenolic contents (TPC; 53 ± 2 mg GAE g-1) and total flavonoid contents (TFC; 26 ± 1 mg QE g-1) were recorded. The major phenolic and flavonoid components were catechol (17.63 μg/mL) and hesperidin (11.37 μg/mL), respectively. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was performed to detect the 7S and 11S globulin‘s molecular mass. The data revealed that red kidney bean protein isolate (KPI) includes two major portions: 7S and 11S globulins. The bioactive compounds of Phaseolus vulgaris were investigated for their antibacterial activities against Enterobacterales for the first time. The protein component (MIC = 0.125 – 2 μg/mL; 53.85%) and its 7S and 11S globulin subunits (MIC = 0.5 – 2 μg/mL; 30.77% each) were the most potent extracts, whereas the methanolic extract was the least effective one (MIC = 2 μg/mL; 15.38%). The results displayed the potential of protein bioactive compounds as a hopeful candidate for enhancing future medication plans for the treatment of Enterobacterales originating from animal and human sources.